Conceptual model of the process of rehabilitating institutional anti-crisis management of enterprises - E. A. Buranova (Russian Journal of Economics and Law)
Objective: to develop the stages of rehabilitation anti-crisis management of an enterprise in order to improve the quality of anti-crisis management in general.Method: abstract-logical.Results: the need to study and implement crisis management is due to insufficient development of issues related to the formation of a set of measures to support enterprises surviving crisis. It is determined that the development of such measures can be based on rehabilitation mechanisms used in various fields. The developed stages of rehabilitation crisis management are in close relationship with the areas of preventive and reactive crisis management. Rehabilitation anti-crisis management is considered not only for the enterprise which overcame a crisis situation, but also for bankrupt enterprises. The increased corporate social responsibility and the company reputation management are studied as elements of institutional and economic rehabilitation of an enterprise. It is proposed to form the strategy of development of the enterprise within rehabilitation anti- crisis management, instead of preventive management. The authors describe further prospects of the enterprise development depending on the implemented process of self-improvement at the enterprise and substantiate the importance of rehabilitation procedures for increasing the efficiency of anti-crisis management.Scientific novelty: the article for the first time reveals in detail the content of each stage of rehabilitation anti-crisis management of an enterprise; describes all the interrelations between them; substantiates the importance of the key actions during each stage of rehabilitation anti-crisis management.Practical significance: implementation of the proposed new stages of rehabilitation anti-crisis management will give a second chance to some entrepreneurs declared bankrupt; using the strategic management tools, it will be possible to ensure anti-crisis sustainability long-term; to lay the need for self-improvement in the foundation of all enterprises’ functioning, making it a natural and necessary element.